Sodobna slovenska dramatika na začetku tretjega desetletja novega tisočletja – kje je in kam z njo? - Komljanec, Kim (Amfiteater (Ljubljana), 2022)
The article offers insight into various approaches to developing contemporary Slovenian playwriting at the beginning of the third decade of the 21st century. It lists existing formal and informal educational opportunities for playwrights, methods of cultivating new writing and various public presentation formats of new Slovenian dramatic writing and the recent development of its staging in Slovenia. The author presents quantitative data on the percentage of Slovenian scripts staged in government-funded theatres and the variations of this percentage over the last two decades. The author’s analysis is based on an extensive questionnaire which includes both quantitative and qualitative research methods examining the processes and circumstances of writing contemporary Slovenian drama from the viewpoints of its various stakeholders: playwrights, translators, dramaturgs, directors, artistic directors and general managers of government-funded public cultural establishments, NGOs or private theatres, editors, publishers, teachers and the representatives of public funding bodies. The findings show a lack of understanding of the creation processes of contemporary Slovenian playwriting by representatives of its peripheral professions (i.e., non-authors). The research results also reveal the consequences of the field’s long-lasting insufficient funding and lack of an expert workforce. Based on the research results, the author proposes possible future directions for the efficient development of contemporary Slovenian playwriting. These proposals include staging, commissioning and long-term theatre residencies for playwrights, as well as establishing a specialised venue aimed exclusively at staging contemporary Slovenian plays.
Keywords: contemporary Slovenian drama; creative writing process; cultural policy; dramsko pisanje; kulturna politika; okoliščine in proces pisanja dramatike; playwriting; sodobna slovenska dramatika; staging; uprizarjanje; writing circumstances